Une méthodologie d’évaluation d’un dispositif d’aide aux primo-entrants à l’université - Isabelle Bournaud; Patrick Pamphile (Revue Internationale de Pédagogie de l’Enseignement Supérieur)
Evaluating a support program has become a major concern for French universities. On the one hand because these programs are part of the struggle against massive failure in undergraduate studies, they are considered as an investment; and on the other hand to improve the quality of training. This article presents an evaluation methodology based on three evaluation criteria identified in the literature: pedagogical effectiveness, efficiency and pedagogical equity. These criteria are evaluated on the basis of indicators calculated on the students’ perception of their level of proficiency in the skills addressed in the curriculum, before and after the program is completed. This methodology is illustrated on a support program for newcomers.